A technological model to define access to electronic clinical records. - Dalley, A.
This communication describes a functioning model that permits access to an electronic health record across a small number of providers resident in an Australian regional setting. Design criteria designated that provider access rights were to be assignable, revokable, transportable, and informable.
Keywords: Australian regional setting; USB I-key.; Clinical knowledge architecture; Electronic clinical record; Health-care document management; Healthcare group; Knowledge sharing; Patient access; Security; Technological model; Unique patient identifier